Impact of The Covid-19 Pandemic for Overstaying in Bali (Law's Application of The Government to Responding People Smuggling) - Adji Priyo Utomo; Fernandez Viky Lieyanto; I Made Dwi Darma Putra Duatra (Jurnal Hukum Prasada, 2022)
This scientific work was created to find out how the regulations are binding on permits for foreigners to stay in the territory of Indonesia and how to handle foreigners who have lived beyond the time limit of the permits granted (overstay) during this pandemic, especially in the Bali area. The research method used is normative juridical, so it can be concluded: bthat the binding regulations regarding overstay are Law No. 6 of 2011 as well as several recently issued regulations regarding residence permits. One of them is Permenkumham number 32 of 2021. From the example of the case in the TPI Denpasar class I immigration office, it can be said that overstay cases during the pandemic are very natural and may even occur periodically due to the effects of a long pandemic. This could be due to overlapping government policies as well as very complex immigration-related regulations during this pandemic and the fragmentation of rules that made it difficult for foreigners in Indonesia to take care of immigration-related matters.